2021
DOI: 10.1186/s12302-021-00455-5
|View full text |Cite
|
Sign up to set email alerts
|

Commercial preparations of pesticides exert higher toxicity and cause changes at subcellular level in earthworm Eisenia andrei

Abstract: Background The environmental impact of pesticides has been an increasingly discussed issue over the last decades. Constant usage of pesticides presents a burden for soil and causes a decrease in its health, including the negative effects on earthworms which are indicators for soil quality. The objective of this research was the assessment of the effects of two insecticides and two herbicides on the earthworm Eisenia andrei. Namely, the following active ingredients and respective commercial prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 58 publications
1
11
0
1
Order By: Relevance
“…Pesticide residue levels in high-fat livestock products can be biomagnified, resulting in greater health risks to humans and other living things [ 9 , 51 ]. These pesticides also affect non-target organisms such as rats, mice [ 52 , 53 ], honeybees [ 54 , 55 ], fish [ 24 , 56 ], earthworms [ 57 , 58 ], and other insects and worms [ 59 ]. Hence, there is growing concern about the potential risks of pesticides to consumers, and public safety has grown in recent years.…”
Section: Resultsmentioning
confidence: 99%
“…Pesticide residue levels in high-fat livestock products can be biomagnified, resulting in greater health risks to humans and other living things [ 9 , 51 ]. These pesticides also affect non-target organisms such as rats, mice [ 52 , 53 ], honeybees [ 54 , 55 ], fish [ 24 , 56 ], earthworms [ 57 , 58 ], and other insects and worms [ 59 ]. Hence, there is growing concern about the potential risks of pesticides to consumers, and public safety has grown in recent years.…”
Section: Resultsmentioning
confidence: 99%
“…Other observations byShoults-Wilson et al (2011) who found that E. fetida consistently avoid soils containing silver nanoparticles Feng et al (2015). studied the effects of thiacloprid on molecular biomarkers (GST, CarE and DNA damage) of E. fetida using the artificial OECD soil for the first time Lackmann et al (2021). reported significant changes for catalase, carboxylesterase and multixenobiotic activities in E. andrei after 48-h exposures to esfenvalerate, thiacloprid and two herbicides.…”
mentioning
confidence: 93%
“…Earthworm Eisenia andrei was chosen as the test organism, due to its widespread usage in ecotoxicology. An earlier study has demonstrated that the commercial formulations of these four pesticides exhibit increased toxicity relative to their active ingredients [21].…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, these formulations impact the earthworm species E. andrei at the subcellular level following a 48-h filter paper test [21]. The main goal was, thus, to investigate the long-term effects of the selected pesticides on a set of biomarkers as well as on reproduction success of E. fetida.…”
Section: Introductionmentioning
confidence: 99%